Pembentukan Karakter Wirausaha Siswa Madrasah Ibtidaiyah Melalui Pekan Wirausaha dan Kreasi Seni - Ahmad Syaifuddin (Jurnal Ilmiah Madrasah, 2024)
This research aims to determine the implementation of the entrepreneurial and artistic creation week program at MI Mambaul Ulum Dagan and the achievement of students' entrepreneurial character values in these activities. A qualitative and descriptive nature defines this research. The data collection techniques used were interviews, observation, and documentation. Based on the results of the data analysis, it shows that the MI Mambaul Ulum Dagan Entrepreneurship and Art Creation Week program was implemented to instill entrepreneurial values in students. The basis for implementing entrepreneurship week activities at MI Mambaul Ulum Dagan is Profiles of Pancasila and Rahmatan lil-alamin students. As a result, the Entrepreneurship Week activities proved to be effective in instilling entrepreneurial values in students. The student behavior that emerged showed that Entrepreneurship Week was also effective in instilling the character dimensions of the Pancasila student profile and the values of Rahmatn Lil-Alamin students.Penelitian ini bertujuan untuk mengetahui pelaksanaan program pekan wirausaha dan kreasi seni di MI Mambaul Ulum Dagan dan ketercapaian nilai-nilai karakter kewirausahaan siswa dalam kegiatan tersebut. Penelitian deskriptif kualitatif ini menggunakan observasi, dokumentasi, dan wawancara untuk mengumpulkan data. Berdasarkan hasil analisis data menunjukkan bahwa program pekan wirausaha dan kreasi seni MI Mambaul Ulum Dagan dilaksanakan untuk menanamkan nilai-nilai kewirausahaan siswa. Landasan pelaksanaan kegiatan pekan wirausaha di MI Mambaul Ulum Dagan adalah profil pelajar Pancasila dan pelajar rahmatan lil-alamin. Hasilnya kegiatan pekan wirausaha terbukti efektif menamkan nilai-nilai kewirausahaan siswa. Perilaku siswa yang muncul menunjukkan bahwa pekan wirausaha juga efektif menanamkan dimensi karakter profil pelajar Pancasila dan nilai pelajar rahmatn lil-alamin.